Perceived Quality Analysis Using Importance Performance Analysis (IPA) Method in Teh Pucuk Harum - Lady Diana Warpindyastuti; Herlin Widasiwi Setianingrum; Megaharti Megaharti (Jurnal Ilmiah Manajemen dan Bisnis, 2023)
Perceived quality of a product is very important because it can be a factor in winning market competition. This study aims to determine what product attributes still need to be improved and which need to be maintained in the Teh Pucuk Harum packaged beverage product. The type of research used is mixed method. Data collection techniques using observation, surveys and interviews. As for data analysis using the Importance Performance Analysis (IPA) method. The results of the research show that the attributes of quality, design, and style still need to be improved and become the focus of the company. Meanwhile, price and feature attributes are considered less important by consumers, so they are not the focus of the company in its marketing strategy.